Enhancing Agriculture through AloT and Data Analytics Middleware (Global Journal of Science Frontier Research, 2024)
Middleware in Agriculture delves into the data analytics role of systematic Artificial Intelligence of Things AIoT in convergence agriculture with smart farming AIoT devices remote diagnostic data analytics platforms data analytics formal recognition and vision learning have generated both the amount and nature of work in rural areas The reason for the developing changes in the global population by age is the bias in the distribution of food resources as well as changes in climate change and the soil condition of compost Data scientists are soon attempting to dive convergence Internet of Things IoT advances in savvy cultivating to support ranchers in producing better seeds crop assurance and manures utilizing AIoT convergence technology 1 This distinguishes consumer-provider-administrator as a service subscriber role on the platform which goes for earning the nation s economy and the profitability of ranchers The central regions where AIoT begins to emerge are agricultural robots scrutiny and soil and yield observation While middleware technology for data analysis is applied there is a great advantage of analyzing regional observation data at a real-time level
Keywords: AIoT middleware; data analytics; systematic literature review; AI technology; agriculture